ANALYSYS OF ASSETS FINANCIAL USING STATISTICAL TOOLS: STANDARD DEVIATION AND CORRELATION COEFFICIENT - Gomero Gonzales, Nicko Alberto (2010)
To make financial decisions that bring to minimizing risks, involves managing a number of economic instruments, mathematical or statistical. From this viewpoint, we can say that the investor call speculator will be better positon with his portfolio, if your selection has been used for the most varied instruments offered by the different scientific disciplines. Either technical or fundamental analysis requires the use of these tools, with these the decisions acceptable, this requirement should be given far more rigorously the characteristics of market interdependence. So then presents the reader with a methodological note for the use of two basic statistical tools to choose the best financial position: The standard deviation and coefficient of correlation.